2016
DOI: 10.1080/15287394.2015.1106994
|View full text |Cite
|
Sign up to set email alerts
|

Assessing differences in toxicity and teratogenicity of three phthalates, Diethyl phthalate, Di-n-propyl phthalate, and Di-n-butyl phthalate, usingXenopus laevisembryos

Abstract: Phthalates, compounds used to add flexibility to plastics, are ubiquitous in the environment. In particular, the diethyl (DEP), di-n-propyl (DnPP), and di-n-butyl (DBP) phthalates were found to exert detrimental effects in both mammalian and non-mammalian studies, with toxic effects varying according to alkyl chain length. Embryos of Xenopus laevis, the African clawed frog, have been used to assess toxicity and teratogenicity of several compounds and serves as a model for assessing adverse and teratogenic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Organisms in the early developmental stages have been reported to be less tolerant to the detrimental effects of pollutants (Huang, Li & Yang, 2016). Many recent publications showed the teratogenic nature of DBP, reporting malformations in developing Zebrafish Danio rerio , the African clawed frog Xenopus laevis , and embryos of the polychaete Galeolaria caespitosa (Xu et al, 2015; Gardner et al, 2016; Lu, Lin & Aitken, 2017). Environmental exposure may lead to DBP accumulation during the neonatal stage, which negatively impacts various future developmental characteristics (Khalil, Elhakim & EL-Murr, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Organisms in the early developmental stages have been reported to be less tolerant to the detrimental effects of pollutants (Huang, Li & Yang, 2016). Many recent publications showed the teratogenic nature of DBP, reporting malformations in developing Zebrafish Danio rerio , the African clawed frog Xenopus laevis , and embryos of the polychaete Galeolaria caespitosa (Xu et al, 2015; Gardner et al, 2016; Lu, Lin & Aitken, 2017). Environmental exposure may lead to DBP accumulation during the neonatal stage, which negatively impacts various future developmental characteristics (Khalil, Elhakim & EL-Murr, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Phthalate esters chosen for analysis (compounds 1 – 15 , Figure 2) include those that have been found in macaroni and cheese powder 25 as well as a variety of other analogues, with the goal of determining the generality of the fluorescence-based method and GC–MS-based analysis across a broad swath of structures with a relatively wide range of potential toxicities. 26 For the fluorescence-based detection method, we selected γ-cyclodextrin as the supramolecular host due to the known ability of cyclodextrin to bind hydrophobic small molecules in its interior 27 and the specific ability of γ-cyclodextrin to facilitate the binding of two small-molecule guests to form a ternary complex. 28 A commercially available boron-dipyrromethene (BODIPY) fluorophore was selected as the source of the read-out signal, based on the well-documented ability of BODIPY fluorophores to display high quantum yield and robust performance under a variety of experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have also observed that phthalate exposures to similar concentrations as used in this study resulted in malformed animals. For example, exposure to DBP and DEP at concentrations exceeding 500 µg/L significantly increased malformations, including abnormal gut coiling, cardiac abnormalities, and malformed faces, eyes, and brains in X. laevis (Bantle et al, 1999;Gardner et al, 2016). Furthermore, S. tropicalis exposed to dimethyl phthalate (DMP) and dicyclohexyl phthalate (DCHP) also resulted in malformations, such as edemas, improperly developed hearts, tail abnormalities, improperly coiled guts, and/or absent gills (Mathieu-Denoncourt et al, 2016).…”
Section: Discussionmentioning
confidence: 99%